Organic matter- and temperature-driven deterministic assembly processes govern bacterial community composition and functionality during manure composting. (15th July 2021) - Bao, Yuanyuan; Feng, Youzhi; Qiu, Chongwen; Zhang, Jianwei; Wang, Yiming; Lin, Xiangui
Graphical abstract: Highlights: Community assembly processes and its governing factors during composting are analyzed. Deterministic assembly processes largely govern community composition for composting. Assembly processes influence metabolic functions via shifts in community composition. OM and temperature govern assembly processes throughout the stages. Abstract: Although many studies have shown that microbial communities play important roles in organic waste composting due to the involvement of specific microbial taxa with metabolic functions, the underlying ecological processes of community assembly and governing factors remain elusive. Thus, a chicken manure composting experiment as a model system of microbially mediated organic waste composting was conducted. Ecological null modeling and metabolic functional prediction combined with electrospray ionization (ESI) Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS) were used to quantify assembly processes governing bacterial community composition and functions during composting. The results showed the predominant role of deterministic assembly processes in shifting community compositions both across and within composting stages. Stochastic assembly processes also concomitantly influenced microbial community compositions. Changes in the organic matter (OM) content and its chemical properties and temperature governed bacterial community assembly processes throughout the stages by selecting specific bacterial taxa such as Cardiobacteriales, Bacteroidales, and Lachnospiraceae on day 1, Firmicutes on days 6, 25 and 37, and Sphingobacteriales, Thermoactinomycetaceae, Actinobacteria, and Novibacillus on day 45. These taxa ultimately influenced community functions such as environmental information processing, carbohydrate and amino acid metabolism, cellular processes, and genetic information processes involved in composting. Taken together, this study indicates that deterministic assembly processes governed by OM content and quality as well as temperature influenced microbial community turnover and determined community functions during composting. These results are important for better understanding and predicting microbial-driven composting and for ultimately manipulating microorganisms for environmentally-friendly composting outcomes.